Cancer, familial cancer and genomics: A primary care perspective. Issue 2 (February 2021) - Hayward, Judith; Kulkarni, Anju; Rafi, Imran
Advances in genomics have vastly increased our understanding of inherited cancer risk and underlying cancer predisposition syndromes, thereby underpinning a revolution in the diagnosis and treatment of cancer itself. Concern regarding family history of cancer is a common presentation within primary care. This article provides an overview of the role of primary care practitioners in the clinical identification and management of inherited cancer risk within primary care including risk assessment, screening and surveillance. The article will consider management issues, including access to genomic testing and advice on risk-reduction measures. The role of genomics in cancer diagnosis and treatment and future applications will be outlined.